2023
DOI: 10.3390/su15118552
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection of High-Speed Railway Box Girder Using Train-Induced Dynamic Responses

Abstract: This paper proposes a damage detection method based on the train-induced responses of high-speed railway box girders. Under the coupling effects of bending and torsion, the traditional damage detection method based on the Euler beam theory cannot be applied. In this research, the box girder section is divided into different components based on the plate element analysis method. The strain responses were preprocessed based on the principal component analysis (PCA) method to remove the influence of train operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The effectiveness of the proposed approach was demonstrated through an application example of a high-fidelity digital twin of the Sado railway bridge in Portugal, reaching minimal false detection incidences of 2%. A similar study was recently reported by Wang et al [43], who investigated the use of strain measurements and the residual errors of an AR model to identify damage in high-speed railway box girders. Although their work demonstrated the potential of strain measurements for damage identification, it did not include a comparison with the results obtained using acceleration data, nor did it investigate the influence of environmental factors.…”
Section: Introductionmentioning
confidence: 55%
“…The effectiveness of the proposed approach was demonstrated through an application example of a high-fidelity digital twin of the Sado railway bridge in Portugal, reaching minimal false detection incidences of 2%. A similar study was recently reported by Wang et al [43], who investigated the use of strain measurements and the residual errors of an AR model to identify damage in high-speed railway box girders. Although their work demonstrated the potential of strain measurements for damage identification, it did not include a comparison with the results obtained using acceleration data, nor did it investigate the influence of environmental factors.…”
Section: Introductionmentioning
confidence: 55%